Use of protexin as a probiotic-supplemented feed additive: assessment of growth, digestibility, serum antioxidant enzyme activity, and blood profile in Cirrhinus mrigala - Riaz, Danish; Hussain, Syed Makhdoom; Sarker, Pallab K.; Ali, Shafaqat; Naeem, Adan; Naeem, Eman; Nazish, Nadia; Al-Anazi, Khalid Mashay; Farah, Mohammad Abul (Frontiers in Sustainable Food Systems, 2024)
Introduction Probiotics, one of functional feed additives (FFAs), have emerged as a potential supplement to strengthen fish health and mitigate oxidative stress. The main focus of our research was to explore the benefits of probiotics (protexin) on growth, digestibility, antioxidant enzyme activity, and blood indices of Cirrhinus mrigala fingerlings. Methods A total of 105 fish (7.42 ± 0.02 g/fish) were used in a 90-day feeding trial. Fish were fed two times a day, and diets were tested in triplicate tanks (15 fingerlings per tank). Moringa oleifera seed meal was chosen as a basal feed ingredient. Seven test diets were formulated: One was control (without supplement), and six diets had different concentrations of probiotics, such as 0.5, 1, 1.5, 2, 2.5, and 3 g kg−1. Results The results of growth and nutrient absorption were maximum at a probiotic concentration of 2 g kg−1. The optimal serum antioxidant enzyme activity and blood parameters were likewise obtained at a probiotic dose of 2 g kg−1. Conclusions Supplementing C. mrigala with 2 g kg−1 probiotics substantially improved their growth, nutrient digestibility, antioxidant enzyme activity, and hematological indices (p < 0.05).